(untitled) (Лучшие интеллектуальные исследования, 2025)
Symptomatic thrombocytopathy refers to a group of disorders characterized by abnormal platelet function, leading to bleeding and thrombotic complications. Unlike thrombocytopenia, where platelet count is low, thrombocytopathy involves normal or elevated platelet counts with impaired function. This condition can be congenital or acquired, with various underlying causes including genetic mutations, autoimmune diseases, and drug-induced effects. Patients often present with mucocutaneous bleeding, easy bruising, and, paradoxically, thrombotic events such as deep vein thrombosis or pulmonary embolism. Diagnosis involves platelet function assays, bleeding time tests, and genetic screening. Management strategies are tailored to the underlying etiology and may include platelet transfusions, antifibrinolytic agents, or immunosuppressive therapy. Early recognition and appropriate treatment are crucial to prevent severe hemorrhagic or thrombotic events.